An Improved Critical Current Calculation Method of HTS Field-Excitation Coil for Double-Stator HTS Generator With Stationary Seal - Wang, Yubin; Wang, Qiusheng; Zhu, Xinkai; Li, Xianglin; Hua, Wei (IEEE transactions on energy conversion, 2023)
In this article, a calculation method for critical current of high-temperature superconducting (HTS) excitation coils made by Bi-2223 tapes is proposed, which can provide a reference for the design and manufacture of HTS excitation coils. Based on the test data provided by the manufacturer, the suppression effect of the applied parallel and perpendicular magnetic field on the critical current density is separately described by the proposed Jc-B model of the Bi-2223 tapes. Then, taking a 10 kW double-stator HTS machine (DS-HTSM) as an example, the target excitation magnetomotive force (MMF) required to meet its designed electromagnetic properties is obtained. After then, the turns number and the critical current of the HTS excitation coils required to meet the target MMF are calculated by the finite element analysis (FEA). Further, the FEA model of the DS-HTSM will be built by using the homogenization modeling method of HTS coils, and the influence of the armature reaction magnetic field on the critical current of the HTS excitation coils is analyzed. Finally, the correctness and effectiveness of the proposed improved critical current calculation method is verified by fabricating the 10 kW DS-HTSM prototype and conducting experimental test.